The Changing Media Environment - Sjöberg, Ulrika (ZER. Revista de Estudios de Comunicación, 2016)
Young people are increasingly having access to their own TV-set, video recorder, or computer. New interactive digital media, like CD-Rom and Internet, are entering contemporary homes. Inspired by the ideas of a present European comparative study ñ the Himmelweit project, my thesis wanted to provide and understanding of Swedish children¥s and teenagers¥use of screen-based electronic media, and how these are intertwined in daily life. It was shown that young people, who spent much time with the peer group or were active in various associations had a low media consumption. The opposite was true for the persons who preferred to stay at home.